Does an In-House Computer-Aided Design/Computer-Aided Manufacturing Approach Contribute to Accuracy and Time Shortening in Mandibular Reconstruction?. Issue 7 (October 2020) - Numajiri, Toshiaki; Morita, Daiki; Yamochi, Ryo; Nakamura, Hiroko; Tsujiko, Shoko; Sowa, Yoshihiro; Toyoda, Kenichiro; Tsujikawa, Takahiro; Arai, Akihito; Hirano, Shigeru
Abstract : Abstract: Mandibular reconstruction using computer-aided design and computer-assisted manufacturing (CAD/CAM) techniques has received recent attention. This technique has theoretical advantages, although this approach can be commercially used in the limited area of the world. The aim is to describe our experience using in-house CAD/CAM guides and the situations in which CAD/CAM may present benefit in the region where commercial guides are unavailable. The authors developed our In-house CAD/CAM approach for mandibular reconstructions with a free fibular flap. Patients were divided into 2 group; CAD/CAM and conventional groups. In the CAD/CAM group, reconstructions were planned virtually using CAD/CAM; these CAD/CAM guides were used in the surgery. In the conventional group, free-hand cutting and fitting of the fibular segments were performed as reconstructions. Later, the bone computed tomographic image was compared with the plan. The averaged deviations and the percentages of the points within 1 mm, 2 mm, and 3 mm deviations were recorded. Total and ischemic time were also recorded. Reconstruction points within 1 mm deviation were 59% of CAD/CAM group (n = 9) and 42% of conventional group (n = 10, P  = 0.04), within 2 mm 82% and 69% ( P  = 0.03). Total time were 1012 and 911 minutes, while flap ischemic time were 147 and 175 minutes ( P  = 0.03), respectively. In-house CAD/CAM mandibular reconstruction also supported accuracy and shorter flap ischemic time. For a detailed accurate reconstruction, CAD/CAM showed superiority than conventional method. Use of the In-house CAD/CAM guides might be an option where commercial guides are not available. Abstract : Supplemental Digital Content is available in the text